Rapid whole-exome sequencing facilitates precision medicine in paediatric rare disease patients and reduces healthcare costs - Claudia C.Y. Chung; Gordon K.C. Leung; Christopher C.Y. Mak; Jasmine L.F. Fung; Mianne Lee; Steven L.C. Pei; Mullin H.C. Yu; Vivian C.C. Hui; Joshua C.K. Chan; Jeffrey F.T. Chau; Marcus C.Y. Chan; Mandy H.Y. Tsang; et al. (Elsevier, 2020)
Background: Rapid whole-exome sequencing (rWES) offers the potential for early diagnosis-predicated precision medicine. Previous evidence focused predominantly on infants from the intensive care unit (ICU). This study sought to examine the diagnostic and clinical utility, and the economic impact on clinical management of rWES in patients beyond infancy and ICU setting. Methods: rWES was performed on a prospective cohort of patients with suspected monogenic disorder referred from territory-wide paediatric ICUs and non-ICUs in Hong Kong urging for rapid genetic diagnosis. All eligible families were invited. We aimed to achieve a rapid turnaround time (TAT) of 14 days. Clinical utility and costs associated with clinical management were assessed in diagnosed cases. Actual quantitative changes in healthcare utilisation were compared with a counterfactual diagnostic trajectory and/or with matched historical control whenever possible. Findings: rWES were offered to 102 families and 32/102 (31%) patients received a molecular diagnosis, with a median TAT of 11 days. Clinical management changed in 28 of 32 diagnosed patients (88%), including but not limited to modifications in treatment, avoidance of surgeries, and informing decisions on redirection of care. Cost analysis was performed in eight patients. rWES was estimated to reduce hospital length of stay by 566 days and decrease healthcare costs by HKD$8,044,250 (GBP£796,460) for these eight patients. The net cost-savings after inclusion of rWES costs were estimated to be HKD$5,325,187 (GBP£527,246). Interpretation: This study replicates the diagnostic capacity and rapid TAT of rWES in predominantly Chinese patients, and demonstrates diagnosis-predicated precision medicine and net healthcare savings. Findings were corroborated by evidence from multinational cohorts, combined as part of a meta-analysis. rWES merits consideration as a first-tier diagnostic tool for patients with urgent needs in the clinical setting. Funding: Health and Medical Research Fund, HKU Seed Fund for Basic Research, The Society for the Relief of Disabled Children, and Edward and Yolanda Wong Fund.